Solitary Osteoma of Femur – A case report (Indian Journal of Case Reports, 2016)
Osteoma is benign tumor usually seen in flat bones. Osteoma usually presents as solitary tumor. It rarely presents as multiple lesion in Gardner’s Syndrome. Osteoma involving long bones is very rare and review of literature showed only a few case reports. We report a case of osteoma involving the shaft of the femur. A 57 year old lady came with swelling over the anterolateral aspect of the thigh. Clinical and radiological examination showed a mass on the anterolateral aspect of the femur. Excision of the lesion was done and the biopsy report showed Osteoma. The patient is free from disease for the past two years. We report this case as osteoma is rare in such a location. Tumor occurring in rare locations need to be thoroughly investigated.